Studies on Monstereae (Araceae) of Peninsular Malaysia I: Rhaphidophora megasperma, a New Record for West Malaysia - Baharuddin, Sulaiman; Boyce, P.C (Universiti Sains Malaysia, 2010)
Rhaphidophora megasperma Engl., a species hitherto regarded as endemic to Sarawak, East Malaysia, is published as a new record for Peninsular Malaysia. It is the first species in the Rhaphidophora Spathacea group recorded for western Sunda. The species is illustrated and a key to the perforate-laminated Rhaphidophora in Peninsular Malaysia is presented.